WWC3: the bridge linking Hippo and Wnt pathways in lung cancer - Ou, Chunlin; Li, Xiayu; Li, Guiyuan; Ma, Jian (Journal of Thoracic Disease; Vol 9, No 8 (August 28, 2017): Journal of Thoracic Disease, 2017)
Lung cancer is the most common cancer worldwide and the leading cause of cancer-related mortality. Despite significant advances towards understanding its causal mechanisms, the morbidity and mortality rates of lung cancer remain high, due to cancer recurrence and metastasis (1).